Everolimus in heart transplantation: an update - Hirt, Stephan W.; Bara, Christoph; Barten, Markus J.; Deuse, Tobias; Dösch, Andreas; Kaczmarek, Ingo; Schulz, Uwe; Stypmann, Jörg; Haneya, Assad; Lehmkuhl, Hans B. (Journal of transplantation, 2013)
The evidence base relating to the use of everolimus in heart transplantation has expanded considerably in recent years, providing clinically relevant information regarding its use in clinical practice. Unless there are special considerations to take into account, all de novo heart transplant patients can be regarded as potential candidates for immunosuppression with everolimus and reduced-exposure calcineurin inhibitor therapy. Caution about the use of everolimus immediately after transplantation should be exercised in certain patients with the risk of severe proteinuria, with poor wound healing, or with uncontrolled severe hyperlipidemia. Initiation of everolimus in the early phase aftertransplant is not advisable in patients with severe pretransplant end-organ dysfunction or in patients on a left ventricular assist device beforetransplant who are at high risk of infection or of wound healing complications. The most frequent reason for introducing everolimus in maintenance heart transplant patients is to support minimization or withdrawal of calcineurin inhibitor therapy, for example, due to impaired renal function or malignancy. Due to its potential to inhibit the progression of cardiac allograft vasculopathy and to reduce cytomegalovirus infection, everolimus should be initiated as soon as possible after heart transplantation. Immediate and adequate reduction of CNI exposure is mandatory from the start of everolimus therapy.